Nuclear IRF-1 expression as a mechanism to assess "Capability" to express PD-L1 and response to PD-1 therapy in metastatic melanoma. Issue 1 (21st March 2017) - Smithy, James W.; Moore, Lauren M.; Pelekanou, Vasiliki; Rehman, Jamaal; Gaule, Patricia; Wong, Pok Fai; Neumeister, Veronique M.; Sznol, Mario; Kluger, Harriet M.; Rimm, David L.
Abstract : Background: Predictive biomarkers for antibodies against programmed death 1 (PD-1) remain a major unmet need in metastatic melanoma. Specifically, response is seen in tumors that do not express programmed death ligand 1 (PD-L1), highlighting the need for a more sensitive biomarker. We hypothesize that capacity to express PD-L1, as assessed by an assay for a PD-L1 transcription factor, interferon regulatory factor 1 (IRF-1), may better distinguish patients likely to benefit from anti-PD-1 immunotherapy. Methods: Samples from 47 melanoma patients that received nivolumab, pembrolizumab, or combination ipilimumab/nivolumab at Yale New Haven Hospital from May 2013 to March 2016 were collected. Expression of IRF-1 and PD-L1 in archival pre-treatment formalin-fixed, paraffin-embedded tumor samples were assessed by the AQUA method of quantitative immunofluorescence. Objective radiographic response (ORR) and progression-free survival (PFS) were assessed using modified RECIST v1.1 criteria. Results: Nuclear IRF-1 expression was higher in patients with partial or complete response (PR/CR) than in patients with stable or progressive disease (SD/PD) ( p =  0.044). There was an insignificant trend toward higher PD-L1 expression in patients with PR/CR ( p =  0.085). PFS was higher in the IRF-1-high group than the IRF-1-low group ( p =  0.017), while PD-L1 expression had no effect on PFS ( p =  0.83). In a subset analysis, a strong association with PFS is seen in patients treated with combination ipilimumab and nivolumab ( p =  0.0051). Conclusions: As a measure of PD-L1 expression capability, IRF-1 expression may be a more valuable predictive biomarker for anti-PD-1 therapy than PD-L1 itself.